Teknologi Pembuatan Sabun Organik Dari Limbah Minyak Goreng Dan Herbal Kebun Tani Pada Kelompok Tani Kosagrha Lestari Surabaya - Sutiyono Sutiyono; Luluk Edahwati; Atika Andini (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This community service program aims to develop a technology for producing organic soap made from used cooking oil and herbal plants from local community gardens as an innovative by-product for the Kosagrha Lestari Farmers Group in Medokan Ayu, Surabaya. The organic soap is produced using used cooking oil processed through a saponification method, combined with local herbal extracts such as lemongrass and mint leaves, which offer skin health benefits. The activity was carried out in the form of training and mentoring sessions for members of the farmers group, focusing on raw material management, soap-making processes, and product marketing strategies. The results showed that the produced soap had good quality and was safe for use. This program not only successfully reduces environmental pollution by utilizing waste cooking oil but also empowers the farmers group by enhancing their entrepreneurial skills. It opens up new market opportunities, improves economic well-being, and supports environmental sustainability by reducing the use of synthetic chemicals..